Evaluation of Fungicides for Controlling Anthracnose on Leaves of Peach Palm (Bactris gasipaes) - Tessmann, Dauri José (2011)
Leaf anthracnose, caused by Colletotrichum loeosporioides, is the most important disease of seedlings and young peach palm plants (Bactris gasipaes). The objective of this study was to evaluate efficacy of some fungicides for controlling anthracnose on leaves of young peach palm (Bactris gasipaes), in Northwestern Paraná State, Brazil. An assay with randomized block design was carried out, with five different fungicides and a control, with four replicates. The fungicide evaluated were: chlorotalonil (2 g L- ), chlorotalonil+methyl tiophanate (1 + 0,4 g L-1), tebuconazole (0,2 g L-1), azoxystrobin (80 mg L-1) and calda Viçosa (boric acid 3 g L-1; copper sulfate 5 g L-1; zinc sulfate 6 g L-1; hydrated lime 3,5 g L-1). Each fungicide was sprayed five times, at 15 to 20- day intervals. All fungicide treatments reduced the disease intensity; however, the most efficient were chlorothalonil and chlorothalonil+methyl thiophanate.